A case report of CIC–DUX4 fusion-positive sarcoma in the pelvic cavity with targeted next-generation sequencing results - Wu, Qian; He, Ying (Frontiers in Oncology, 2022)
CIC–DUX4 fusion-positive sarcoma is a subtype of undifferentiated small round cell sarcoma that is rarely reported. As far as we know, less than 200 cases have been reported worldwide to date. The clinicopathologic characteristics of this kind of tumor are non-specific, which makes it difficult to be diagnosed. Therefore, more cases are required to enrich the diagnosis and treatment experience. Here, we present a 17-year-old Asian girl diagnosed with CIC–DUX4 fusion-positive sarcoma after targeted next-generation sequencing. Her clinical manifestation was abdominal pain. Furthermore, a mass in the pelvic cavity and massive ascites were found after an imaging examination. After resection, the mass was sent to the pathology department for a definite diagnosis, and the micromorphology showed an undifferentiated sarcoma with massive necrosis. The tumor cells were round to spindle with clear to eosinophilic cytoplasm and vesicular nuclei. Rhabdoid cells and myxoid mesenchyme were focally shown. Immunohistochemical staining showed diffusely positive for vimentin, cyclin D1, Fli-1, and WT-1 and very focally positive for CD99. Moreover, the targeted next-generation sequencing also revealed other genetic changes in this tumor including LongInDel of POLE, copy number variation of CD79, low tumor mutational burden, and microsatellite stability. With a follow-up time of 6 months, the patient survived the disease and received chemotherapy routinely. This report presented a rare primary site CIC–DUX4 fusion-positive sarcoma (CDS) and revealed novel genetic changes that enrich the manifestation, histology, and cytogenetic scales of this rare sarcoma. In addition, we have summarized the clinicopathologic characteristics of this tumor by reviewing the literature to have a better understanding of CIC–DUX4 fusion-positive sarcomas, which may be helpful for diagnosis and treatment.